الآثار الحرارية والتنافس بين الأطوار المغناطيسية في بعض خلائط الزجاج السبيني الثنائية ( ذهب – حديد) (Latakia University Journal -Basic Sciences Series, 2018)
According to use of nano (10-9) dimensions in modern experimental techniques, thermal transition investigations carried out on AuFe spin glass alloys, with concentration range (0.1% - 15% per magnetic impurity), and thermal spectrum (0.01- 300 K). Because there is no one source that can give all exact experimental information, we got data from many resources (resistivity, specific heat, susceptibility, Mossbauer effect, neutron scattering, magnetization and hysteresis cycles, NMR, SR ),and obtain a new experimental thermal magnetic phase diagram . A conflict with theoretical studies has been found, because spin glass theory is a new theory and has not yet  complete. The aim of this search is to compare between tow era, modern nano era, and old micro era technology, in no doubt, nano technology will give fine data, and hyperfine information. في إطار دخول التقنيات التجريبية الحديثة مرحلة أبعاد العينات من مرتبة النانو()، جرت اختبارات التحول الحراري على خلائط ذهب-حديد ، في المجال التركيزي (%0.1 - 15%) للشائبة المغناطيسية، والمجال الحراري(0.01 – 300 كلفن) ،ونظرا لاستحالة الحصول على كافة المعلومات من مصدر تجريبي واحد، ووفق عدة مداخل تجريبية] المقاومية الكهربائية،السعات الحرارية، الطواعية(الحساسية)المغناطيسية، أثر موسباو، انتثار النيترون، التمغنط ودورة البطاء المغناطيسي[، تم دراسة ورسم مخطط الطور المغناطيسي الحراري بين تغيرات درجات الحرارة وتركيز الشائبة المغناطيسية في الخليطة، أعطت الدراسة منظورا جديدا للتحولات لا يتوافق مع الدراسات النظرية بشكل دقيق، وذلك بسبب أن نظرية الزجاج السبيني الحديثة العهد لم تكتمل بعد. يهدف البحث إلى إظهار دور تقنية النانو في الأبحاث الحديثة حيث أن هذه التقنية تعطي معلومات فائقة الدقة ونتائج أكثر وطوحا بالمقارنة مع التقنيات السابقة (تقنية المايكرو 10-6).